Coping Successfully with Dyslexia: An Initial Study of an Inclusive School‐Based Resilience Programme. (21st March 2013) - Firth, Nola; Frydenberg, Erica; Steeg, Charlotte; Bond, Lyndal
<x xml:space="preserve">Abstract</x> A dyslexia coping programme entitled Success and Dyslexia was implemented in two primary schools within a whole‐class coping programme and whole‐school dyslexia professional development context. One hundred and two year 6 students, 23 of whom had dyslexia, undertook surveys pretest, post‐test and at 1‐year follow‐up. Effectiveness of the coping programme and maintenance of effects for the students after transition to secondary school were investigated. Inclusion of contrast group data in the follow‐up year suggested significant positive changes at first and second follow‐ups in locus of control and nonproductive coping may also be associated with increase in age. Most trends were in the expected direction, especially for students with dyslexia. At follow‐up, students with dyslexia reported similar perceived control and adaptive coping to students without dyslexia rather than a decrease in these areas as is usually the case. A larger sample and an ongoing control group are needed to confirm these results. Copyright © 2013 John Wiley & Sons, Ltd.